Methodology of Experimental Research of Hydroseeding Process of Gemitated Grain - Deyneka, S.; Aniskevich, L.; Kushnarov, S.; Kovalov, Oleksandr; Ковальов, Олександр Вікторович; Ковалев, Александр Викторович (My University, 2018)
The population of Ukraine is not provided with a sufficient number of vegetables. Insufficient amount of moisture in spring needs to improve the technology of vegetable crops sowing. The work is devoted to the experimental study of the possibility to seed sprouted vegetable grain together with liquid. The article deals with the process of hydroseeding of germinated grain in which the most effective working parameters of the hydroseeder are realized. A new technological scheme for mixing of the seed mixture without traumatization of sprouters with the help of a mixing chamber of aerodynamic action is studied. The proposed designs of hydroseeders and sowing machines due to their imperfections did not find implementation into production. The analysis of existing structures indicates that the degree of their introduction is the result of low evenness of seeding and high damaging of sprouts. The experimental research program includes determination of the even distribution of seeds in the mixing chamber in the conditions of various air pressures and water levels in the chamber, determination of the evenness of seeding depending on the number of seeds in the mixing chamber, determination the seed lifting speed depending on the size characteristics, determination of the optimal loss rate of the water and seed mixture in the hydroseeding process. The article deals with the materials of laboratory tests of the stationary experimental model of the hydroseeding apparatus. The research was conducted in the stationary mode with the use of modern equipment and methods of conducting scientific studies with the help of computer technologies. The purpose of experiments includes the definition of empirical coefficients that are determined by the test results. On the base of the conclusions on the article materials it is possible to develop of an optimal field research plan which can confirm the scientific hypothesis of the dependence of the evenness of seeding of germinated grain on the evenness of their distribution in the mixing chamber. The interconnection of the structural and technological parameters of the seeding process of the hydromixture with the efficiency of the technological process is experimentally proved.
Keywords: experiment; plan of the experiment; installation; factor randomization; empirical coefficients